Vietnamese Rice Expressions: A Socio-cultural Analysis - Ngoc Binh, Nguyen (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
People can hear the word ’rice’ every day, everywhere in the world. A study on rice expressions affirms its importance in daily life and/or in history, and by human consideration or belief, especially in the Southeast Asian area. This article researches the socio-cultural perspectives in Vietnamese rice expressions by analyzing a total of 776 Vietnamese rice expressions. This article argued that the concept of rice, a culture-bound symbol embedded in Vietnamese people life, expressed many facets of life, including society, economy, politics and Vietnamese identity. Received 3rd April 2018; Revised 26th April 2018; Accepted 30th April 2018